Impact of threading dislocations in GaN p–n diodes on forward I–V characteristics. (21st September 2020) - Ohta, Hiroshi; Asai, Naomi; Horikiri, Fumimasa; Narita, Yoshinobu; Yoshida, Takehiro; Mishima, Tomoyoshi
Abstract: The correlation between on-resistance ( R on ) and the number of dislocations under the anode electrode was evaluated using p–n junction diodes on a high-quality GaN substrate with an average threading dislocation density of ≤4 × 10 5 cm −2 by a newly developed maskless 3D method. A positive correlation was observed between R on and the number of dislocations. The microdiodes with an anode electrode size of diameter 6 μ m of having one dislocation and no dislocation under the anode electrode were evaluated to estimate the current reduction by one dislocation, which was derived to be about 0.37 mA at a forward voltage of 5 V. The reduction of the forward current seemed to be caused by non-radiative recombination centers around dislocation lines which weakened the photon recycling effects and conductivity modulation. On the other hand, there was no clear correlation between the breakdown voltage and the number of dislocations.